Solvent Extraction of Fe(III) from Aqueous Chloride Solution by Cyanex 301 Dissolved in Kerosene - Biswas, R. K.; Ali, M. R.; Habib, M. A.; Salam, S. M. A.; Karmakar, A. K.; Ullah, M. H. (Journal of Scientific Research, 2010)
The title system has been investigated over a wide range of aqueous acidity. The equilibration time is 1 h. The extraction ratio (D) is independent of [Fe(III)] provided equilibrium [HCl] and [HA] are kept constant. At a constant equilibrium extractant concentration, the [HCl] dependences are -1.6, 0 and -3 in the [HCl] regions of >3, 2-0.5 and <0.3 M; respectively; whilst at constant [HCl], the [HA] dependence is 3.0. On the other hand, [Cl-] dependence varies within -0.5 to -3 at constant [HCl] of 0.3 M; whereas its values are -1 and 0.63 at constant [HCl] of 3 and 1 M, respectively. Based on these results the extraction mechanisms have been suggested to be + 3 HA(o) ? FeA3(o) + n Cl- + 3 H+ in the low [HCl] region, + 3 HA(o) + n Cl- ? FeCl3.3HA(o) in the intermediate [HCl] region and HFeCl4 + 3 HA(o) ? FeCl3.3HA(o) + HCl in the high [HCl] region under investigation. The Kex and ΔH values have been evaluated. Loading capacity is 5.5 g Fe(III)/100 g Cyanex 301. The stripping can be made effective by a mixture of 6 M H2SO4 and 1 M Na2C2O4. Keywords: Extraction equilibrium; Fe(III) extraction; Cyanex 301; chloride medium. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.6263 J. Sci. Res. 3 (1), 97-109 (2011)